Area‐Minimizing Currents mod 2Q: Linear Regularity Theory. Issue 1 (30th November 2020) - De Lellis, Camillo; Hirsch, Jonas; Marchese, Andrea; Stuvard, Salvatore
Abstract: We establish a theory of Q ‐valued functions minimizing a suitable generalization of the Dirichlet integral. In a second paper the theory will be used to approximate efficiently area minimizing currents m od ( p ) when p = 2 Q, and to establish a first general partial regularity theorem for every p in any dimension and codimension . © 2020 Wiley Periodicals LLC.